Importance of choosing vegetation for the urban road network: a literature review (Research, Society and Development, 2020)
The expansion of urban centers caused the replacement of natural areas, reducing the vegetated areas to small islands or bands that accompany the urban road network. These green areas, although small, are essential, since they contribute to the ecological quality of the urban environment and the quality of life of the population. Thus, the objective of the present work was to carry out a literature review regarding the importance of the correct choice of vegetation and to indicate botanical species to compose the urban road network. The methodology used consists of a bibliographic search in a library and in scientific electronic addresses, using the keywords such as: “urban afforestation”, “urban green spaces”, “importance of vegetation”, “urban landscaping” and “vegetation for urban road network”. After analyzing this research, it was found that the introduction of vegetation in urban centers carries a cultural and social character, in Brazil this process has gained importance since the 19th century, mainly due to the expansion of urban centers. The road monitoring green is part of the urban infrastructure, and is often the responsibility of the government. The floristic composition of these areas varies according to region and with different physical and environmental aspects. The appropriate choice of vegetation to compose the urban centers will allow the success, the preservation and the permanence of the botanical species, besides increasing the quality of life of the citizens.